Student Needs Analysis of the Scientific Literacy Oriented Interactive Multimedia on Living Cells Matter - Sigit Subagja; Bibin Rubini; Indarini Dwi Pursitasari (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Scientific literacy defines as multidimensional skills that students should have to prepare a life after school. One thing that can improve scientific literacy is the quality of teaching materials. Teaching materials are one of the main components in learning including living cell matter. Currently, teaching materials that are widely used in Indonesia are still in the form of printed teaching materials and according to PISA results, these teaching materials have not a significant impact on students' scientific literacy. Nowadays, technological advances are very rapid and have a very positive impact on life, including in education. One of the benefits is the integration of interactive multimedia as the basis for teaching materials. The purpose of this article is to analyze the students' needs regarding interactive multimedia-based teaching materials containing scientific literacy in the learning of the living cells matter and to analysis of scientific literacy aspects in the previously used teaching materials. The research method used is descriptive qualitative with data collection techniques using questionnaires and interviews. The research subjects used were 3 Biology teachers and 81 students of class XI of science program at one of high schools in Sukabumi City, Indonesia. The results showed that students need interactive multimedia-based teaching materials containing scientific literacy on living cell matter and currently the teaching materials that students use have several components that are not as expected and the components of scientific literacy in these teaching are still not balanced. Therefore, it is necessary to develop interactive multimedia-based teaching materials containing scientific literacy on living cell matter to improve students' scientific literacy.